Kebijakan Pendidikan Sekolah Dasar Kabupaten Buleleng, Bali Melalui Analisis Kondisi Nyata - Luh Tu Selpi Wahyuni; Nyoman Ayu Putri Lestari; I Made Aditya Dharma; Ida Bagus Putu Arnyana; Nyoman Dantes (Universitas Negeri Padang, 2023)
Education is an important aspect of human existence as it promotes human enhancement in the emotive, cognitive, and psychomotor domains. The implementation of an educational wisdom model can be in the form of ideas, outlines, diagrams, or numerical states that are used to clarify, clarify, and present parts of a real instructional problem. Therefore, this study aims to conduct a mini-research to share suggestions about educational wisdom. This research method is descriptive quantitative. The research location was in all primary schools in Buleleng Regency. The object of the research was primary schools in Buleleng district. The research subjects were students and teachers in Buleleng district. The results of the study showed a low student-teacher ratio, namely Banjar sub-district 16.59, Buleleng sub-district 17.71, and Busungbiu sub-district 14.74 with this low ratio interpreted as the three sub-districts having an excess of primary school teachers. Ideas for intelligence that can be provided include the ideal ratio of students to teachers must be met, as well as school facilities, complete and appropriate learning facilities, teacher availability and competence, principal availability and competence, service personnel availability and competence, labour availability and competence, librarian availability and competence, and the ideal ratio of students to teachers. It is recommended to education policy managers to match the actual needs in primary schools that refer to the 8 education standards.